Linguistic politeness from an ethological perspective: Theoretical questions and empirical issues - Wacewicz, Sławomir; Żywiczyński, Przemysław; McCrohon, Luke (Theoria et Historia Scientiarum, 2015)
Linguistic politeness (LP) refers to the set of “linguistic features mediating norms of social behaviour, in relation to such notions as courtesy, rapport, deference and distance” (Crystal 2008). Although researchers (e.g. Eelen 2001, Watts 2003) agree that it is intimately connected to normativity, group hierarchy and cooperation – the core questions of human ethology and human behavioural ecology – linguistic politeness has largely been neglected from those perspectives (Eibl-Eibesfeldt 1989 being a notable exception). In this paper we spell out the significance of a naturalistically oriented study of LP, outline a research agenda, and identify a number of methodological problems whose resolution is a prerequisite for such an approach.